(3GdQGeRI aj Ydej GdYQhV hGdbGajIs - (3GdNRQLj, CHh eMeO, VjGA GdOjf, YHO Gddg Hf eMeO, (B626 (3g`s ((3eOQSI GdefbGQj HeOjfI GScOGQs)
(3ChdgG (B:s
(3hddTYQ ejRGf Sej YQhVg , HgG GdfbU hGdQLMGf jOQjgeG GdaJi , hCfhGYg bd NeSI YTQ cdgG , JDda ef LRFjf aQYjf dG Shis
(3BNQgG (B:s
(3hbO cedJ SJ hJSYjf aGdPj (B*** (3JhSY aj PG GdYde JhSYg MHG , hjSCd YHO Gddg PG GdNRQLj ef (B*** (3eWGdYgG EJMGag efg HGdOYGAs
(3aj Chdg fbhd aj GddZI hGdJaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 124s
(3eYLe GdeDdajf(B: 1 / 460s
(3cTa GdXfhf(B: 1 / 830s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGajs